MENGANGKAT TANGAN KETIKA BERDO’A (ANALISIS KONTRADIKSI HADITH) - Siswanto, Hery (UNIVERSUM, 2017)
It starts from two hadith in Sunan Ibn Majah book related to the way of praying. The first hadith explains that the Prophet SAW prays without lifting hands except when istisqo’ prayer; meanwhile, the second hadith shows the Prophet’s instruction to shahabat to lift hand when absolutely praying. From those contradiction hadith, there are some problems as follows: 1) how is the quality of sanad and matan of those hadith of ibn Majah? 2) how is the hadith hujjah? 3) how is appropriate ta’wil toward those hadith? The methods used in this research are takhrīj al-ḥadīth and hadith contradiction (Mukhtalif al-ḥadīth) methods. The research findings are first the quality of sanad hadith ibn Majah no.1180 is ḥasan li dhātih, while the quality of sanad hadith ibn Majah no. 1181 is al-ḍa’īf; second, both hadith Ibn Majah no. 1180 and 1181 can become hujjah. However, the difference is that the first hadith can be the basis in taking law since the hadith status is ḥasan li dhātih. Meanwhile, the second hadith can become hujjah if its quality improve become hadith ḥasan li ghayrih with other hadith having similar meaning. Third, the contradiction of matan hadith Ibn Majah no. 1180 and 1181 shows various methods including in tanawwu’ fi al-‘ibādah category (diversity in praying). Keywords: Ibn Mājah, contradiction, Hadith, lifting hand